PENGARUH TERAPI PUZZLE WAPUWAN TERHADAP FUNGSI KOGNITIF LANSIA DI POSYANDU SETYAMANUNGGAL III - Margiyati Margiyati; Tria Friska Ningrum; Ainnur Rahmanti; Mimin Indah Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2021)
The elderly are at risk of experiencing cognitive function disorders due to the aging process. Wapuwan Puzzle (Wayang Punakawan) is a game therapy that was developed to improve cognitive function by carrying elements of the art of wayang punakawan characters that are popular with the elderly. The purpose of this study was to analyze the influence of the Wapuwan Puzzle on the cognitive function of the elderly. The design of this study was a quasi-experimental with a pre-post design with a control group. The research sample was 38 elderly people using the total sampling technique at the Posyandu Setya Manunggal III. Research instrument using MMSE. Data analysis using Mann Whitney. The results showed that the gender characteristics of the majority of the respondents were female, the average age of the respondents was in the range of 60-74 years, and the education of the respondents was on average not attending school and completing elementary school. The MMSE score of the elderly who received the Wapuwan Puzzle increased significantly than the elderly who did not receive the Wapuwan Puzzle. The results of the Mann Whiteney test obtained a significance value of 0.000 (P value < 0.05) so that it was concluded that there was an effect of the application of the Wapuwan Puzzle on the increase in cognitive function in the elderly at the Setyamanunggal Posyandu III Lempuyangan Hamlet.